Recent developments in desensitization of crossmatch-positive kidney transplant recipients - Morath, Christian; Opelz, Gerhard; Zeier, Martin; Süsal, Caner (Transplantation proceedings, 2012)
Currently, there are two major options for the successful and timely transplantation of sensitized kidney transplant recipients: (1) avoidance of the sensitization barrier using special allocation programs, or (2) desensitization. In the case of broadly sensitized kidney patients, a combination of both options might be necessary. This review focuses on new advances in desensitization of crossmatch-positive kidney transplant recipients which include immunoadsorption and the administration of new substances such as the complement C5 inhibitor eculizumab. Finally, integrated algorithms that combine different measures are acknowledged.